Finite-element simulation of explosion proof junction box by ABAQUS - Wang, Zhao (2016)
In the hazardous area, explosion often occurs due to the tiny substances presented in the air, such as flammable gases flammable liquid-produced vapours, combustible liquid-produced vapours, combustible dusts, or ignitable fibre/flying. As such, all the electrical and electronic equipment installed in the hazardous area are required to meet strictly requirement of the standard, i.e. ATEX, IECex [2]. One of the explosion proof method for electrical and electronic equipment makes use of the type of “Ex d” flameproof junction box [2], which houses the electrical and electronic components inside, and has metal walls with the thickness of 4 ~10 mm. If there is any arcing contact due to the components, it isolates inside the junction box and prevents it from the explosion. In the market of various explosion proof equipment, all the manufacturers for the type of Ex d junction box are required to follow the regulation of international organizations to produce safe products [2]. However, currently no manufacturer designs and optimizes the junction box via software for simulation of explosion dynamics. In the present work, the finite-element based software, ABAQUS, is used for simulation of Ex d proof junction box subject to explosion loading. The purpose of this FYP project is to validate if the junction box is qualified to meet the minimum requirement of explosion proof standard, given by IEC 60079-0 [2], in order to protect critical equipment installed inside, and to identify the weak point based on the current design of the junction box. In the present project, three cases are conducted via ABAQUS to examine the working scenarios of Ex d proof junction box, namely Case 1: A loading of 2 MPa imposed on the surface of the box cover for 10 seconds; Case 2: Explosion occurring at a scaled distance of 0.5m/kg1/3 outside from the junction box; Case 3: Explosion occurring inside the junction box with 10, 20 and 50 bars, respectively. Based on the simulation and discussion, the design of junction box is optimized, and the two recommendations are thus given via the present FYP project. In particular, the wall of the junction box is redesigned with the optimized thickness of 8 mm, and the screws are redesigned with the optimized diameter of 10 mm.